Implementation of a vancomycin therapeutic monitoring protocol in adults - Heckler, Adriane Maris; Hahn, Siomara Regina (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and objectives: Therapeutic Drug Monitoring (TDM) is an important tool in optimizing vancomycin therapy, a drug used to treat serious infections caused by grampositive bacteria. The aim of this study was to implement a protocol for the therapeutic monitoring of vancomycin in hospitals and to describe the clinical, laboratory and use characteristics of this drug after its implementation. Methods: The international consensus on vancomycin TDM was used for protocol development. Patient data were collected from medical records and pharmacokinetic software estimates. Results: The vancomycin protocol was implemented at a hospital and made available to the clinical staff. We evaluated 49 patients. Vancomycin was prescribed mainly to treat pneumonia 15 (30.6%). Among the identified microorganisms, Staphylococcus aureus was the most common with 8 cases (50%), and 9 (56.3%) patients were resistant to oxacillin. The average use of vancomycin was 10.6 (± 6.6) days and the loading dose was administered in 33 (67.3%) patients. A total of 5 (11.1%) patients had acute renal failure. Monitoring of Minimal Concentrations in the vancomycin valley (Cmin) occurred in 43 (87.8%) patients. In the first measurement, 16 of them (37.2%) presented Cmin below 10 mcg/dL and 11 (25.6%) above 20 mcg/dL, data considered outside the therapeutic range. Conclusion: The elaboration of an MTF protocol for vancomycin guides the rational and safe use of this antibiotic. Continued training in human resources and investment in dose-adjusting pharmacokinetic software may contribute to the optimization of vancomycin therapy.